2019
DOI: 10.48550/arxiv.1904.10026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Random trees in the boundary of Outer space

Ilya Kapovich,
Joseph Maher,
Catherine Pfaff
et al.

Abstract: We prove that for the harmonic measure associated to a random walk on Out(Fr) satisfying some mild conditions, a typical tree in the boundary of Outer space is trivalent and nongeometric. This answers a question of M. Bestvina.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In [AKKP19], it is shown that the axes of principal fully irreducible outer automorphisms share a certain "stability" property with principal pseudo-Anosov axes in Teichmüller space. This stability property is then used in [KMPT18] and [KMPT19] to not only prove which outer automorphisms are random walk generic, but to understand properties held by a typical (with respect to the harmonic measure) tree in the boundary of Outer space.…”
Section: Introductionmentioning
confidence: 99%
“…In [AKKP19], it is shown that the axes of principal fully irreducible outer automorphisms share a certain "stability" property with principal pseudo-Anosov axes in Teichmüller space. This stability property is then used in [KMPT18] and [KMPT19] to not only prove which outer automorphisms are random walk generic, but to understand properties held by a typical (with respect to the harmonic measure) tree in the boundary of Outer space.…”
Section: Introductionmentioning
confidence: 99%